Flipped Learning in Higher Education for the Development of Intrinsic Motivation: A Systematic Review - Rebeca Kerstin Alonso; Alexander Vélez; María Carmen Martínez-Monteagudo; Markel Rico-González (MDPI AG, 2023)
Background: Flipped learning (FL) is being considered, in terms of new educational trends, a beneficial pedagogical model in the classroom. In particular, FL and intrinsic motivation (IM) are key components to the model since they can be crucial to a high-quality education. FL for the development of IM in higher education, as well as searches for potential interventions have, thus improved over the past ten years. However, no reviews that analyze the findings and conclusions reached have been published. Consequently, the objectives of this paper were to analyze the relationship between the use of FL and the IM of students in higher education, and to identify the aspects that should be present in FL models to develop the IM that contributes to high-quality education. Methods: in accordance with PRISMA guidelines, a systematic review of PubMed, Web of Science, Scopus, and ProQuest was carried out. Results: Of the 407 studies that were initially discovered, 17 underwent a full examination in which all findings and conclusions were analyzed. After implementation, the majority of the FL interventions improved IM results. Conclusion: many key aspects have been identified that must be followed in order to intrinsically motivate students using the FL methodology.